Sneak-App Quality Measurement Using FURPS Model and Euclidean Distance - Zaky, Muhammad; Shaliha, Ratih Mar’atus; Nuraji, Diaz; Ardian Shafa, Rr Azzahra; Purbaningtyas, Rani (Journal of Telematics and Informatics, 2025)
Ensuring the quality of Sneak-App is crucial for supporting the operations of Sneak Crafters, a Small and Medium Enterprise (SME) specializing in custom sneakers. This study evaluates the Sneak-App's quality using the FURPS model (Functionality, Usability, Reliability, Performance, Supportability) combined with the Euclidean Distance method. The assessment involved distributing questionnaires to 20 respondents, utilizing a Likert scale (1–4) to measure each FURPS sub-indicator. The results indicate that Sneak-App achieved a final quality score of 65%, categorizing it as a moderately good application. Among the five indicators, Reliability recorded the highest score (93%), indicating strong system stability, while Functionality (55%) and Supportability (56%) had the lowest scores, suggesting the need for improvements in feature completeness and system adaptability. These findings validate the effectiveness of the FURPS model and Euclidean Distance method in identifying software strengths and weaknesses. By addressing key areas for improvement, developers can enhance the application's overall usability and performance. This research provides valuable insights for future software development, emphasizing the need for continuous quality enhancement to optimize Sneak-App's role in automating business processes for SMEs.